Protein-Protein Interaction Among the FoxP Family Members and their Regulation of Two Target Genes, VLDLR and CNTNAP2 in the Zebra Finch Song System - Mendoza, Ezequiel; Scharff, Constance (Frontiers in Molecular Neuroscience, 2017)
The Forkhead transcription factor FOXP2 is implicated in speech perception and production. The avian homologue, FoxP2 , contributes to song learning and production in birds. In human cell lines, transcriptional activity of FOXP2 requires homo-dimerization or dimerization with paralogues FOXP1 or FOXP4. Whether FoxP dimerization occurs in the brain is unknown. We recently showed that FoxP1, FoxP2 and FoxP4 (FoxP1/2/4) proteins are co-expressed in neurons of Area X, a song control region in zebra finches. We now report on dimer- and oligomerization of zebra finch FoxPs and how this affects transcription. In cell lines and in the brain we identify homo- and hetero-dimers, and an oligomer composed of FoxP1/2/4. We further show that FoxP1/2/4 bind to the regulatory region of the target gene CNTNAP2 and FoxP1/4 to the regulatory region of VLDLR. Interestingly, FoxP1/2/4 individually or in combinations regulate the promoters for SV40, zebra finch VLDLR and CNTNAP2 differentially. These data exemplify the potential for complex transcriptional regulation of FoxP1/2/4, highlighting the need for future functional studies dissecting their differential regulation in the brain.